ANCIENT MODERN BRAND â€œTHE TIMESâ€ - Kacharava, Khatuna (European Scientific Journal, ESJ, 2016)
The worldwide newspaper The Times does not change its principles even in XXI century. Its managing editor George Brock (1981-2008) considers that we do not have to expect that even such a respectable newspaper as The Times will be able to maintain status quo. He states: â€œEvery newspaper tries to change a chemical process without exploding a laboratory. A newspaper should match with societyâ€™s character and a readerâ€™s tasteâ€. The Times was the first newspaper that chose this title. It was established on January 1, 1785. At that period it was named as â€œThe Daily Universal Registerâ€. In 1788 it was renamed as â€œThe Times of Universal Registerâ€. Later, the title was shortened and the newspaper was called simply â€œThe Timesâ€. In 1981 The Times faced a hard period. It was losing readers and advertisement income. Namely at that period Rupert Murdoch's News International bought The Times and The Sunday Times from Thomson. The acquisition followed three weeks of intensive bargaining with the unions by company negotiators, John Collier and Bill O'Neill. After this, Murdoch made the decision to modernize The Times and save the British newspaper industry from â€œgloomyâ€ Medieval darkness. Notwithstanding great competition, The Times, that is the origin of print media, still manages to be traditional and modern at the same time.